An Overview of the Religiosity of Adolescents at GMIT Efata Liliba Church. - Djurumanna, Marselinda Rambu Djola Piras; Benu, Juliana Marlin Y.; Mage, Mernon Yerlinda Carlista (Universitas Nusa Cendana, 2024)
Religiosity includes beliefs and religious teachings, religious practices, commitment and identity, participation in religious communities, spiritual experiences, and the application of ethics and morality, which vary according to the intensity and manner in which individuals practice their faith. This study aims to describe the dimensions of religiosity—belief, connection, behavior, and togetherness—among adolescents at GMIT Jemaat Efata Liliba. The research employs a qualitative method. To obtain accurate data and information, the study uses interview techniques for data collection. Purposive sampling is used for participant selection, with a total of 6 adolescents from GMIT Jemaat Efata Liliba. Involvement in religious activities is influenced by parental guidance and social interactions, providing both personal and social benefits, and fostering a deep relationship with God. This study illustrates how various aspects of religiosity affect and shape the religious experiences of adolescents.